Image processing of an agriculture produce: Determination of size and ripeness of a banana - Mustafa N.B.A.; Fuad N.A.; Ahmed S.K.; Abidin A.A.Z.; Ali Z.; Wong B.Y.; Sharrif Z.A.Md. (2023)
Over the last several decades, customers' lifestyles and needs have gone through tremendous changes. These changes are new challenges for the farmers whose produce has to meet the customers' demands. The ability to classify agriculture produce based on size and quality is not only going to help the farmer but also the customer. This will help the farmer to grade the fruit, the seller to price it optimally and the customer value for money. Bananas are classified according to sizes, shapes, textures, colors and taste. The process of getting the size and ripeness of a banana is done from its image using the Image Processing Toolbox in MATLAB. These features are important to determine the optimal size and ripeness. From the size, the grade and type of the banana can be determined. The percentage of ripeness can be determined by evaluating the individual pixels of the image. 2008 IEEE.